Cost of oral cholera vaccine delivery in a mass immunization program for children in urban Bangladesh. (December 2022) - Sarker, Abdur Razzaque; Khan, Ashraful Islam; Islam, Md. Taufiqul; Chowdhury, Fahima; Khanam, Farhana; Kang, Sophie; Ahmmed, Faisal; Im, Justin; Kim, Deok Ryun; Tadesse, Birkneh Tilahun; Ahmed, Tasnuva; Aziz, Asma Binte; et al.
Highlights: Estimation of the cost of an OCV campaign targeting children is important for policy implication. Vaccine price was the highest cost driver among the variable costs. Cost difference can be attributed to the scale and location of vaccination. Abstract: Cholera poses a substantial health burden in the developing world due to both epidemic and endemic diseases. The World Health Organization recommends oral cholera vaccines for mass vaccination campaigns in addition to traditional prevention practices and treatments in resource-poor settings. In many developing countries like Bangladesh, the major challenge behind implementing mass vaccination campaigns concerns the affordability of the oral cholera vaccine (OCV). Vaccination of children with OCV is not only an impactful approach for controlling cholera at the population level and reducing childhood morbidity but is also considered more cost-effective than vaccinating all ages. The aim of the study was to estimate the cost of an OCV campaign for children from a societal perspective using empirical study. A total of 66, 311 children aged 1 to 14 years old were fully vaccinated with two doses of the OCV Shanchol while 9, 035 individuals received one dose of this vaccine. The estimated societal cost per individual for full vaccination was US 6.11, which includes the cost of vaccine delivery estimated at US 1.95. The cost per single dose was estimated at US 2.86. The total provider cost for full vaccination was estimated at US 6.01 and the recipient cost at US 0.10. Our estimation of OCV delivery costs for children was relatively higher than what was found in a similar mass OCV campaign for all age groups, indicating that there may be additional cost factors to consider in targeted vaccine campaigns. This analysis provides useful benchmarks for the possible costs related to delivery of OCV to children and future OCV cost-effectiveness models should factor in these possible cost disparities. Attempts to reduce the cost per dose are likely to have a greater impact on the cost of similar vaccination campaigns in many resource-poor settings.